The Effect of Internal Control, Organizational Commitment, and Utilization of Information Technology on the Quality of Financial Statements with Organizational Culture as a Moderating Variable - Fariz Akbar; Fachruzzaman; Lismawati (Indonesian Journal Economic Review (IJER), 2026)
This study examines the effects of internal control, organizational commitment, and information technology (IT) utilization on the quality of financial statements, with organizational culture as a moderating variable. Grounded in stewardship and task-technology fit theories, survey data were collected from 120 financial personnel across 40 Regional Work Units (SKPD) in Central Bengkulu Regency and analyzed using PLS-SEM. The results indicate that internal control (β=0.231, p=0.004), organizational commitment (β=0.272, p=0.004), and IT utilization (β=0.320, p=0.001) significantly and positively affect the quality of financial statements. Furthermore, organizational culture acts as a pure moderator that significantly strengthens the impact of internal control (β=0.242, p=0.012), organizational commitment (β=0.231, p=0.003), and IT utilization (β=0.315, p=0.002). The model accounts for 88.9% of the variance in financial statement quality (R²=0.889). These findings imply that technical systems and behavioral factors produce optimal reporting outcomes when embedded within an accountability-driven institutional culture.